Association of clonal hematopoiesis mutations with clinical outcomes: A systematic review and meta‐analysis. Issue 4 (19th January 2022) - Nowakowska, Malgorzata K.; Kim, Taebeom; Thompson, Mikayla T.; Bolton, Kelly L.; Deswal, Anita; Lin, Steven H.; Scheet, Paul; Wehner, Mackenzie R.; Nead, Kevin T.
Abstract: Clonal hematopoiesis (CH) mutations are common among individuals without known hematologic disease. CH mutations have been associated with numerous adverse clinical outcomes across many different studies. We systematically reviewed the available literature for clinical outcomes associated with CH mutations in patients without hematologic disease. We searched PubMed, EMBASE, and Scopus for eligible studies. Three investigators independently extracted the data, and each study was verified by a second author. Risk of bias was assessed using the Newcastle‐Ottawa Scale. We identified 32 studies with 56 cohorts that examine the association between CH mutations and clinical outcomes. We conducted meta‐analyses comparing outcomes among individuals with and without detectable CH mutations. We conducted meta‐analyses for cardiovascular diseases (nine studies; HR = 1.61, 95% CI = 1.26–2.07, p  = .0002), hematologic malignancies (seven studies; HR = 5.59, 95% CI = 3.31–9.45, p  < .0001), therapy‐related myeloid neoplasms (four studies; HR = 7.55, 95% CI = 4.3–13.57, p  < .001), and death (nine studies; HR = 1.34, 95% CI = 1.2–1.5, p  < .0001). The cardiovascular disease analysis was further stratified by variant allele fraction (VAF) and gene, which showed a statistically significant association only with a VAF of ≥ 10% (HR = 1.42, 95% CI = 1.24–1.62, p  < .0001), as well as statistically significant associations for each gene examined with the largest magnitude of effect found for CH mutations in JAK2 (HR = 3.5, 95% CI = 1.84–6.68, p  < .0001). Analysis of the association of CH mutations with hematologic malignancy demonstrated a numeric stepwise increase in risk with increasing VAF thresholds. This analysis strongly supports the association of CH mutations with a clinically meaningful increased risk of adverse clinical outcomes among individuals without hematologic disease, particularly with increasing VAF thresholds.